Fatores de risco para eventos adversos respiratórios em adultos submetidos à cirurgias não cardíacas e não torácicas - Badessa, Marianne Peixoto Sobral Giroldo [UNIFESP] (2019)
Justifications and objects: Adverse respiratory event is the highest class of anesthesia complications associated with high mortality. Therefore, it is important to identify the risk factors associated with these complications. This study was made to establish the principal factors of risk in intraoperative respiratory complications. Method: This retrospective descriptive research was combined with anesthesiology reports performed in the University Hospital complex in the city of São Paulo during a 6-year period. The presence of bronchospasm, apnea, dyspnea, hypoventilation, hypoxia, pneumothorax, re-intubation or accidental extubation were considered as adverse intraoperative respiratory events. Incompleted anesthesia reports with adverse events were excluded. The univariate and multivariate analysis were performed by the logistic regression model considering the stepwise variable selection technique. The significance threshold was set at p<0,05. Results: A total of 43,383 anesthetics for noncardiac and non-thoracic surgeries were performed in patients aged 18 years or older. There was a record of 401 (0.92%) anesthesias in which there was at least one intraoperative respiratory adverse event. The most frequent respiratory events were bronchospasm (n = 157, 39.2%), hypoxia (n = 110, 27.4%) and hypoventilation (n = 81, 20.2%). The following were identified as risk factors for the presence of adverse events (p <0.05): male gender (OR 1.68; IC95% 1,13- 2,51), physical health ASA P3 (OR 1.862; IC95% 1,470-2,360), ASA P4 (OR 3.266; IC95% 2.326-4.585), ASA P5 (OR 5.642; IC 95% 3.201-9.945), head and neck surgery (OR 2.927; IC 95% 2.060-4.157, gastrointestinal surgery (OR 1.591; IC95% 1.237-2.046), otorhinolaryngological surgery (OR 1.821; IC95% 1.295-2.561), general anesthesia (OR 2.934; IC95% 2.30-3.742) and presence of the first year resident of anesthesiology. Conclusions: The incidence of adverse intraoperative respiratory events in adult patients undergoing noncardiac and non-thoracic surgeries is low. It is essential that the risk factors intrinsic to the patients, anesthetic technique and surgical specialty is tracked in the preoperative period in order to plan strategies to reduce such intraoperative events.